The changing role of Government research institutes in innovation systems - Guinet, Jean (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Recent years have seen an intensified discussion in many OECD countries about the role and mission of public research in the innovation system. This discussion takes place in quite specific national contexts, but should benefit from international experience. However, whereas voluminous literatures address the changing governance methods, organizational forms and missions of universities, much less attention has been devoted to developing a common understanding of the challenges faced by non-university public research institutions. The main goals of this paper is to contribute to clarifying the nature of these challenges, outlines possible policy answers and draws some implications for Korea. In the first section, the paper uses available internationally comparable indicators to review trends in the contribution of government research institutes (GRIs) to R&D and innovation activities. In the second section, the paper identifies the current major changes in the dynamics of innovation that may call for further adjustments in the positioning, organization and steering of public research institutes. Finally, the paper outlines some strategic objectives and orientations for the reform of public research institutes as part of the broader agenda of the Korean innovation strategy.